Genomic insights into the cold adaptation and secondary metabolite potential of Pseudoalteromonas sp. WY3 from Antarctic krill - Wang, Yuanyuan; Xie, Jinxuan; Feng, Zhengqi; Ma, Linbo; Wu, Wenbo; Guo, Changjun; He, Jianguo (Frontiers in Microbiology, 2024)
In the Antarctic marine ecosystem, krill play a pivotal role, yet the intricate microbial community intertwined with these diminutive crustaceans remains largely unmapped. In this study, we successfully isolated and characterized a unique bacterial strain, Pseudoalteromonas sp. WY3, from Antarctic krill. Genomic analysis revealed that WY3 harbors a multitude of genes associated with cold shock proteins, oxidoreductases, and enzymes involved in the osmotic stress response, equipping it with a robust molecular arsenal to withstand frigid Antarctic conditions. Furthermore, the presence of two distinct biosynthesis-related gene clusters suggests that WY3 has the potential to synthesize diverse secondary metabolites, including aryl polyenes and ribosomally synthesized and post-translationally modified peptides. Notably, the identification of genes encoding enzymes crucial for biological immunity pathways, such as apeH and ubiC, hints at a complex symbiotic relationship between WY3 and its krill host. This comprehensive study highlights the robust potential of WY3 for secondary metabolite production and its remarkable ability to thrive at extremely low temperatures in the Antarctic ecosystem, shedding light on the interplay between culturable microorganisms and their hosts in harsh environments, and providing insights into the underexplored microbial communities associated with Antarctic marine organisms and their role in environmental adaptation and biotechnological applications.